2009
DOI: 10.1007/s00251-009-0387-6
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II polymorphism is associated with a canine SLE-related disease complex

Abstract: Nova Scotia duck tolling retrievers are predisposed to a SLE-related disease complex including immune-mediated rheumatic disease (IMRD) and steroid-responsive meningitis-arteritis (SRMA). IMRD involves symptoms that resemble those seen in systemic autoimmune rheumatic diseases, such as systemic lupus erythematosus, SLE, or SLE-related diseases, in humans. This disease complex involves persistent lameness, stiffness, mainly after resting, and palpable pain from several joints of extremities. The majority of aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 26 publications
0
51
1
Order By: Relevance
“…[45][46][47] We 48 and others [49][50][51][52][53][54] have used the anti-mouse/rat Foxp3 antibody clone FJK-16s to identify a population of canine CD4 + T cells that phenotypically resembles Treg cells, but direct evidence for regulatory activity has remained elusive. 55 In this study, we have characterized the phenotype and function of canine CD4 + CD25 high FOXP3 high T cells in vitro, providing direct evidence for the regulatory function of this T-cell subset in dogs -an important veterinary species that also serves as a model for several human diseases, including a number of cancers, [56][57][58] systemic lupus erythematosus 59,60 and several genetic diseases of the haemopoietic system. 61 …”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 97%
“…[45][46][47] We 48 and others [49][50][51][52][53][54] have used the anti-mouse/rat Foxp3 antibody clone FJK-16s to identify a population of canine CD4 + T cells that phenotypically resembles Treg cells, but direct evidence for regulatory activity has remained elusive. 55 In this study, we have characterized the phenotype and function of canine CD4 + CD25 high FOXP3 high T cells in vitro, providing direct evidence for the regulatory function of this T-cell subset in dogs -an important veterinary species that also serves as a model for several human diseases, including a number of cancers, [56][57][58] systemic lupus erythematosus 59,60 and several genetic diseases of the haemopoietic system. 61 …”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 97%
“…SRMA has been described as occasionally occurring concurrently with immune-mediated polyarthritis (Webb and others 2002, Tipold and Schatzberg 2010). Genetic studies have indicated an inherited connection between the diseases, IMRD and SRMA, in Tollers (Wilbe and others 2009, 2010).…”
mentioning
confidence: 99%
“…In earlier studies of Tollers with both SRMA and the SLE-related disease complex, several genes have been identified and one locus seems to be shared between the disease complexes (Wilbe and others 2009, 2010). Further genetic studies are in progress in order to in more detail identify, validate and functionally define the causative mutations.…”
mentioning
confidence: 99%
“…A Vogt-Koyanagi-Harada-like syndrome of Akita dogs has a strong association with certain alleles and allele combinations of DLA class II genes, 1 as does autoimmune hemolytic anemia, 20 immune arthritis, 28 hypothyroidism in several breeds, 25,26,38 type I diabetes mellitus in Samoyed dogs and Cairn and Tibetan Terriers, 23 anal furunculosis of German Shepherd Dogs, 5 and systemic lupus erythematosus-related complex of Nova Scotia Tolling Retrievers. 37 Necrotizing meningoencephalitis (NME) of Pug dogs 10 and Addison disease in Nova Scotia Duck Tolling Retrievers 12 have been recently added to this growing list. Dog leukocyte antigen class II associations have also been described for visceral leishmaniasis 30 in domestic dogs in Spain and for generalized demodicosis in Boxer, Argentinean Mastiff, and mixed-breed dogs in Argentina.…”
Section: Introductionmentioning
confidence: 99%